The Application of UTAUT Modified Model to Analyze the Customers Use Behavior of Shopee Paylater - Asri Ady Bakri; Darwis; Anita Bawaiqki Wandanaya; Vivid Violin; Tribowo Rachmat Fauzan (SEULANGA SYSTEM PUBLISHER, 2023)
Paylater is one of the newest payment methods in e-commerce that implements a buy now, pay later system or an installment mechanism. This service is the latest payment option launched by e-commerce. This study aims to determine user acceptance perceptions that influence satisfaction, sustainability intentions, and user use behavior. The Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model, which also includes the variables perceived trust and pleasure, was employed in this study. This study adopted a quantitative methodology, distributing online surveys with 26 questions and using SmartPLS version 3.3.2 tools to analyze the data. According to the study's findings, eight out of ten hypotheses are supported. Effort Expectancy on Satisfaction and Price Value on Satisfaction are two hypotheses that are ruled out since their path coefficients and T-test values, respectively, are less than 0.1 and 1.96.